Financial innovations and sanitation services: the battle between low-income users and shareholders - De Oliveira, Alberto (Bulletin of Geography. Socio-economic Series, 2020)
This article aims to show how changes in the model for financing basic sanitation affect social inequality and urban segregation, and to discuss alternatives that minimise the impact these changes have on low-income populations. The investigation focuses on mediations between sanitation policy and general urban policies in the more ample process of valorising capital, involving different scales of geography and forms of state action. Widespread privatisation and public–private partnerships have altered the role that rates charged to users play in financing sanitation systems. This, in turn, has an impact on low-income populations’ access to these systems. The study concludes that new models of financing tend to privilege spaces in the city that are attractive to private capital, and that investments in sanitation are supported by financial innovations that depend on the collective force of remunerating shareholders and maintaining investors’ expectations. Finally, the article approaches solutions that ensure low-income families’ access to public services, with special emphasis on subsidised rate systems based on the stratification of urban areas adopted in Colombia. The article concludes that this experiment presents both positive and negative aspects that may serve as starting points toward potential solutions for Brazil.